Impact of Maternal Risk Factors on Birth Weight of Newborn in Two Maternity Hospitals in Baghdad City - jeid, Shukria; Abbas, ikbal (Iraqi National Journal of Nursing Specialties, 2006)
Objectives: A cross sectional analytic study was carried out to identify the maternal risk factors which contribute to occurrence of low birth weight, and to determine the statistical significant differences between low birth weight and maternal risk factors. Methodology: A purposive sample of (400) woman was selected from AL-Elwyia Maternity Teaching Hospital and Fatima Al-Zaharia Maternity and Pediatric Teaching Hospital. Data was collected through the interview of mothers. Questionnaire format was designed and consisted seven parts, demographic variables, and reproductive variables , Reproductive health variables, complications during the current pregnancy, the mother newborn variables nutritional status for the mother , antenatal care services, and the psychosocial status for pregnant women. Validity and reliability of the questionnaire were determined by conducting a pilot study. Descriptive and inferential statistical procedures were used to analyze the data. Results: The results of the study revealed that the most of them their age was ranged between (20-34) years, and the highest percentage of them were graduated of primary school and less, most of them were housewives with low socioeconomic status. The result indicated that there were five important variables contributed to the incidence of low birth weight and these variables were gestational age nutrition status, previous low birth weight, and psychosocial status for pregnant women during pregnancy and the age of mothers. Recommendations: it is recommended to emphasize on prenatal care as early as possible and improve health services rendered to mothers during pregnancy that the nurse must take the role in reducing the incidence of LBW.